Podatek od wartości dodanej (VAT) w Unii Europejskiej - koncepcja, rozwój i wybrane problemy - Prinz, Aloys (Value Added Tax (VAT) in the European Union: Concept, Development and Some Problems, 2005)
Creation of the Common Market within the EU resulted in some problems related to the taxation of goods and services. In particular, this is the case of VAT since its collection across national borders requires the control at these borders if the VAT follows the so called destination principle. According to this principle, the VAT is to be collected in that country where goods or services arc consumed. For that reason, exports are VAT-free and imports are taxed at the borders. Abolishing border controls requires a complex control system in order to secure the VAT payment in international transactions. Subsequent to that, different tax rates in national VAT systems and weaknesses in the border control enable the misuse of the VAT system. To avoid this crucial question is whether the commodity destination principle should be replaced by the origin principle. Another question is whether the VAT rates should be harmonized among the EU countries. In contrast to that, in the subject literature an alternative solution, and namely the so called VIVAT, has been proposed. It is discussed in the paper. The paper's final conclusion is that the VIVAT might be a viable solution without giving up the commodity destination principle. However, with respect to some new problems being caused by the Internet, the transition to the origin principle may turn out to be inevitable.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 194-210